System Design of 3-phase Balance -Compensation Device in Traction Power Supply for EMU Test Line - 蒋家久; 陈志博; 沈辉; 王才孝 (Kongzhi Yu Xinxi Jishu)
EMU test line supplies 25 kV voltage to single -phase traction load from 10 kV boosting. The 3-phase balance-compensation system of the power supply is used based on the SVC dynamic reactive compensation. It introduces balance-compensation theory, composition structure of the compensation devices, parameters selection and balance control of this system. The stability issues are also explored. Furthermore, TSC circuit’s parameters are optimal selected by simulation. The compensative method is novel and the performance of the system is excellent.